The Role of Memorable Tourism Experiences on Revisit Intention Through Visitor Engagement at the Lodge Maribaya - Natasyari Daeli; Yadi Ernawadi (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of hedonism, meaningfulness, aesthetics, and safety on revisit intention, with visitor engagement as a mediating variable, among tourists at The Lodge Maribaya. A total of 108 visitors at The Lodge Maribaya participated in the quantitative survey that formed the basis of this study. The author used partial least squares (PLS) modeling based on Smart PLS 3.0 to analyze the data collected from the questionnaire. The findings show that although the safety factor does not play a mediating role in revisit intention, the factors of hedonism, meaningfulness, and aesthetics all play a mediating role through visitor engagement. The results of this study are expected to provide input for the management of The Lodge Maribaya to prioritize strengthening the aspect of hedonism, followed by aesthetics, and then meaningfulness, in order to increase tourists’ revisit intention through visitor engagement. Further research is needed to develop a study model that includes additional variables more relevant to the context of adventure and nature tourism. This will help the author gain a deeper understanding of the factors influencing revisit intention, as the study’s findings suggest that factors not included in the model may influence revisit intention.